GPS-derived slant water vapor for cloud monitoring in Singapore - Heh, Ding Yu (2023)
This paper presents a GPS-derived slant water vapor technique for cloud monitoring in Singapore. The normalized slant wet delay ((Formula presented.)) and slant water vapor ((Formula presented.)) are introduced. The suitability of the normalized (Formula presented.) over (Formula presented.) for cloud monitoring is demonstrated, as it is not very sensitive to the satellite elevation angle. For better illustration and representation of the spatial distribution of the normalized (Formula presented.), the skyplot is discretized into different cells based on the azimuth and elevation angles to produce the spatial plot. The spatial plots are analyzed for cloud monitoring and compared alongside the sky images. The results show that the spatial plots of normalized (Formula presented.) are generally consistent with the cloud formation observed in the sky images, hence demonstrating their usefulness for cloud monitoring. The probability distribution of the normalized (Formula presented.) associated with cloudy and clear sky conditions is also analyzed, which shows that the mean values of normalized (Formula presented.) associated with the former are higher. Finally, the time series of the normalized (Formula presented.) is explored in relation to the solar irradiance. It is shown that the time series and spatial plots of normalized (Formula presented.) are also consistent with the ratio of clear sky to measured irradiance.